ANALISIS EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHA TANI SINGKONG GAJAH DI KECAMATAN RANTAU PULUNG - Akbarrizki, Muzizat (Jurnal Magrobis, 2017)
The research was conducted from February up to May 2017. The aims of this research is to know the level of influence of production factors of land area, seeds, fertilizer and labor to the number of cassava production and to know the level of technical efficiency, price efficiency and economic efficiency. Analysis model used is production function Cobb Douglass and efficiency calculation. Level of influence Factors of production to the number of elephant cassava production is calculated by multiple linear regression analysis using aplication program SPSS 16. The results of the research mentioned simultan eously (F test) with 10% error rate of factors of production have a significant effect on the number of cassava production, partially (T test) shows that the factor of land area production has a positive but not significant effect on the number of cassava production, No significant effect on the production of cassava while labor production factors significantly affect the production of cassava. Keywords: efficiency, production factors, farming, cassava.